High pressure cooling in the machining of hard-to-machine materials - Kramar, Davorin (Strojniški vestnik, 2009)
This paper investigates the application of high-pressure cooling (HPC) assistance in the rough turning of two different hard-to-machine materials, namely hard-chromed and surface hardened C45E and Inconel 718 with coated carbide tools. The region of operability - technology windows, which sets the boundaries of the process parameters, has been experimentally determined using the tool-material pair (TMP) methodology. The capabilities of different hard turning procedures are compared by means of chip breakability, cooling efficiencz, temperatures in cutting yone, tool wear and cutting forces. All machining experiments were performed under conventional cutting speeds.
Keywords: hlajenje; odrezavanje; obdelovalnost; obraba